Mind the Gap: Student Researchers Use Secondary Data to Explore Disparities in STEM Education - Nathan Bean; Amanda Gnadt; Nicole Maupin; Sherry A. White; Lori Andersen (Prairie Journal of Educational Research, 2016)
Large data sets offer opportunities for graduate students to become involved in meaningful research, but also comes with a unique set of challenges. This paper seeks to examine that relationship through utilizing the High School Longitudinal Study 2009 – representative of US ninth graders in 2009 (n = 21,444) – to examine a set of research questions about STEM interest and preparation amongst secondary students. Student researchers identified gaps in plans and outcomes with regards to race, gender, exceptionalities, and socioeconomic status. Findings indicated inequities that affect STEM outcomes. A significant interaction was found between students education expectations by gender on science self-efficacy [F(4,1264) = 2.797, p =.025]. This interaction was not observed for math self-efficacy. Females and underrepresented minorities were less likely to pursue computer science courses and computer science careers [Females: Χ2 (2, N = 20,594) = 111.500, p < .0001; Minorities: Χ2 (2, N = 13,069) = 6.455, p = .040]. Students’ expectations for post-secondary education differed by IEP status and socioeconomic status [Χ2 (3, n =165,684) = 26.886, p = 0.001]. Finally, time spent in extracurricular activities impacted academic achievement and students in lower socioeconomic groups were less involved in extracurricular activities [Χ2 (4, n = 20,598) = 132.298, p < .0001].
Keywords: STEM; equity; under representation; gender; disability; extracurricular activities; K-12; graduate education; large data sets